Analisis Kesesuaian Materi Bakteri pada Buku Teks dengan Kompetensi Dasar Kurikulum 2013 - Sri Utami; Tri Jalmo; Berti Yolida (Universitas Lampung, 2018)
This study aims to describe the level of conformity of bacteria materials in Biology textbooks of High School Grade X with basic competence Curriculum 2013 reviewed in terms of breadth and depth of the material. This research was a qualitative research by using documentation study. The object of this research was A book published by Erlangga and B book published by Yrama Widya. Suitability data obtained from the analysis of bacterial material in textbooks, then analyzed descriptively qualitative. The results showed that the level of the suitability of bacteria material with basic competence of Curriculum 2013 in A book categorized as